2021
DOI: 10.1021/acs.organomet.1c00074
|View full text |Cite
|
Sign up to set email alerts
|

DFT Approach for Predicting 13C NMR Shifts of Atoms Directly Coordinated to Nickel

Abstract: The aim of this work is to develop a simple density functional theory (DFT) method that can be safely applied to calculate 13C NMR shifts in diamagnetic Ni complexes. A comparative analysis of calculated vs experimental 13C NMR shifts for a wide range of nickel complexes (157 in total) was carried out. A number of functional–basis set combinations were tested. On the whole, the NMR shifts of carbon atoms directly bonded to nickel can be calculated within the framework of the Kohn–Sham theory level using a numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 110 publications
1
18
0
Order By: Relevance
“…For evaluation purposes, the TPSSTPSS functionals, the def2-TZVPP basis set, the IEFPCM solvent model, the ultrafine integration grid and the GIAO method were adopted as ''fixed parameters'' when the other factors were studied. The mean absolute error (MAE) is the chosen parameter in order to evaluate the general fitting goodness between the computed and experimental data sets: The experimental chemical shifts were recovered from the literature, below the references for each compound: [1,2,3,4,5,6,7,16,17,18,19,20,21,22, Pt-Me, Pt-iso, Pt-u], 31 [8,9,10], 85 [11,12] 86 [13,14,15,24,25], 87 [23], 88 [a, b]. 83 For practical reasons, when signals were identified as overcrowded unresolved resonances, the average value was taken into consideration.…”
Section: Computational Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…For evaluation purposes, the TPSSTPSS functionals, the def2-TZVPP basis set, the IEFPCM solvent model, the ultrafine integration grid and the GIAO method were adopted as ''fixed parameters'' when the other factors were studied. The mean absolute error (MAE) is the chosen parameter in order to evaluate the general fitting goodness between the computed and experimental data sets: The experimental chemical shifts were recovered from the literature, below the references for each compound: [1,2,3,4,5,6,7,16,17,18,19,20,21,22, Pt-Me, Pt-iso, Pt-u], 31 [8,9,10], 85 [11,12] 86 [13,14,15,24,25], 87 [23], 88 [a, b]. 83 For practical reasons, when signals were identified as overcrowded unresolved resonances, the average value was taken into consideration.…”
Section: Computational Sectionmentioning
confidence: 99%
“…20 Although in silico , theoretical specialists have focused their efforts on NMR simulations of molecules cointaining atoms belonging to the first three rows of the periodic table, 21 theoretical predictions of chemical shifts of NMR active nuclei in organometallic compounds are still in their infancy. 22,23…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Absolute NMR shielding scales in methyl halides were derived from experimental and calculated nuclear spin-rotation constants. 42 Latypov et al 43 reported on accurate prediction of 13 C nuclear shieldings for atoms directly coordinated to diamagnetic nickel ion. Rusakova and Rusakov 44 analyzed 77 Se and 125 Te NMR structure parameters as well as their structural applications by quantum mechanical calculations.…”
Section: Theory and Development Of Toolsmentioning
confidence: 99%
“…116 DFT calculations as support of NMR experimental data were also used for structural characterization of phosphate species adsorbed on g-alumina. 117 Among rarely used NMR nuclei is 43 Ca. On the other hand, calcium ion is widely distributed in construction materials, as well as in biomaterials.…”
Section: Nuclear Shielding Prediction In Natural Productsmentioning
confidence: 99%